Romance languages and linguistic theory 16 selected papers from the 47th Linguistics Symposium on Romance Languages (LSRL), Newark, Delaware - Vogel, Irene, 1952- (Romance languages and linguistic theory,, 2020)
"The chapters in this book represent the theme of "bridges" - bridging research approaches and directions across languages, methodologies and disciplines. Alongside descriptive and theoretical studies, the contributions present experimental studies addressing issues in syntax, phonetics-phonology and sociolinguistics. Alongside investigations of linguistic phenomena in standard Romance language varieties, other investigations address less well-known and studied, minority and endangered varieties (e.g., Quebec French, Brazilian Portuguese, Romanian, Galician, Catalan and Palenquero) from both synchronic and diachronic perspectives. Romance languages in contact with other languages and bilingualism, now also integral aspects of the field, are reflected in this volume as well, including less well-known cases of contemporary contact of Serbian with Romanian, and earlier contact of African languages with Spanish and Portuguese. This volume thus continues the decades long tradition of the Linguistic Symposium on Romance Languages of embracing cutting-edge developments in the field"--